Perindopril and hydrochlorthiazide effects on endothelium-dependent vasodilatation and angiotensin-converting enzyme activity in patients with mild to moderate arterial hypertension - T. V. Aparina; A. N. Britov; O. A. Gomazkov; O. N. Yakimenko; T. V. Ektova; E. A. Dilakyan (Кардиоваскулярная терапия и профилактика)
Aim. During 12-week perindopril (PR) and hypothiazide (HT) therapy, to study its antihypertensive efficacy, as well as its influence on endothelial function (EF) and angiotensin-converting enzyme (ACE) serum activity, in patents with essential arterial hypertension (EAH). Material and methods. The study included 20 males (mean age 48.8±8.4 years) with mild to moderate AH. Antihypertensive efficacy was assessed during office BP measurement (Korotkoff method) and 24-hour blood pressure monitoring (BPM). EF was assessed by endothelium-dependent vasodilatation (EDVD) during reactive hyperemia test (RHT). Results. According to office BP measurements, target BP level (<140/90 mm Hg) was achieved in 75% patients on PR monotherapy, and 65% on HT monotherapy. According to 24-hour BPM, PR influenced BP levels more beneficially than HT. During PR and HT monotherapy, antihypertensive effect was more pronounced in patients with moderate AH (p=0.06). PR monotherapy caused some EDVD increase in patients with moderate AH (by 10%; NS), but did not affect EDVD in individuals with mild AH. HT treatment substantially increased EDVD in patients with mild AH (by 24%, from 7.13 to 9.18) and even more in participants with moderate AH (by 54%, from 6.52 to 10.02). PR therapy significantly reduced ACE activity, increased at baseline, to 28.1 nmol/min•ml (-43%, p<0.01). In patients with initially low ACE activity, it remained at the same level (reduction to 21.16 nmol/min•ml, NS). HT treatment did not affect this parameter in participants with low or high initial ACE activity. Conclusion. PR and HT antihypertensive effects were associated with EDVD correction. PR and HT antihypertensive efficacy depended on baseline ACE activity. Both drugs could be used for BP correction in individuals with low ACE activity; for patients with initially high ACE activity, PR is more effective.